1996
DOI: 10.1177/027112149601600305
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Analysis of Parents' and Service Coordinators' Descriptions of Variables That Influence Collaborative Relationships

Abstract: Parent-professional collaboration is an essential component of successful early intervention efforts. A collaborative relationship exists when both parents and professionals view each other as partners, with both providing expertise and knowledge that will help the family reach its goals. Although collaborative relationships are valued within early intervention, little is known about the variables that enhance or detract from collaboration. The purpose of this study was to examine parents' and service coordina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 14 publications
4
61
0
1
Order By: Relevance
“…Dinnebeil, Hale, and Rule (1996) identified personal characteristics and beliefs considered central to successful collaboration, such as friendliness, family-centered beliefs, integrity, commitment, and communication skills. Summers et al (2001) found interpersonal factors such as sensitivity to parents, clarity, and respect were valued by parents and staff involved in collaborations between early intervention (Part C of Too often partnerships between families and professionals ftill short of recommended practice.…”
Section: Partnershipsmentioning
confidence: 99%
“…Dinnebeil, Hale, and Rule (1996) identified personal characteristics and beliefs considered central to successful collaboration, such as friendliness, family-centered beliefs, integrity, commitment, and communication skills. Summers et al (2001) found interpersonal factors such as sensitivity to parents, clarity, and respect were valued by parents and staff involved in collaborations between early intervention (Part C of Too often partnerships between families and professionals ftill short of recommended practice.…”
Section: Partnershipsmentioning
confidence: 99%
“…Participants said they desired nonhierarchical relationships where equality, reciprocity, interdependence, and collaboration were valued and appreciated by both families and professionals (Blue-Banning et al, 2004;Cunningham & Davis, 1985;DeChillo et al, 1994;DeChillo, Koren, & Mezera, 1996;Dunst & Paget, 1991;Knox et al, 2000;Turnbull et al, 2000;. They hoped professionals would become families' reliable allies, embodying qualities of empathy, commitment, and trustwor-26O thiness (Blue-Banning et al;Dinnebeil, Hale, & Rule, 1996;Dunst & Paget;Freire, 1970;Knox et al). Participants also touched upon an emerging notion of "human reciprocity" and of "a moral position collectively recognizing that we each, as human beings, possess a unique value that adds to and strengthens the cultural fabric of society" (Kliewer, 1998, p. 4) in defining the meaning of equality, human values and contributions, and human relationships.…”
Section: Partnershipsmentioning
confidence: 99%
“…The information gathered through these information sheets is summarized in Tables 3 and 4. school psychologists) and parents (Dinnebeil, Hale, & Rule, 1996;Dunst & Paget, 1991;Turnbull & Turnbull, 1997). These discussions fail to mention paraeducator-parent relationships regarding the education of students with disabilities.…”
Section: Data Collectionmentioning
confidence: 99%